How to cheat your own death : a novel [large type] - Perrin, Kristen (Perrin, Kristen. Castle Knoll murder mystery, 2026)
"Some secrets are deadlier than others. 1968: Frances Adams is loving her new London life, and she's stepped into a world of glamour thanks to her new friend, Vera Huntington--a magnetic socialite as mysterious as she is provocative. Vera dances around London like she owns it, taking Frances with her. Present day: When Annie Adams heads to London to visit her famous artist mother, Laura, the last thing she expects to find is a dead body. Least of all for it to be Laura's new protégée, left in an alley with her heart surgically removed from her chest. Annie is no stranger to murder--after all, she's solved a few already. And something about this case feels familiar. She's read about one just like it, in the journals of her late great aunt Frances, whose friend Vera was killed in the 1960s in the exact same way. As Annie investigates, threats pile up on Laura's doorstep, and it soon becomes clear that she's next. With her mother's life on the line, can Annie find the killer before it's too late?"--